2017
DOI: 10.1242/jcs.204529
|View full text |Cite
|
Sign up to set email alerts
|

L-leucyl-L-leucine methyl ester does not release cysteine cathepsins to the cytosol but inactivates them in transiently permeabilized lysosomes

Abstract: L-leucyl-L-leucine methyl ester (LLOMe) induces apoptosis, which is thought to be mediated by release of lysosomal cysteine cathepsins from permeabilized lysosomes into the cytosol. Here, we demonstrated in HeLa cells that apoptotic as well as sub-apoptotic concentrations of LLOMe caused rapid and complete lysosomal membrane permeabilization (LMP), as evidenced by loss of the proton gradient and release into the cytosol of internalized lysosomal markers below a relative molecular mass of 10,000. However, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(92 citation statements)
references
References 47 publications
10
71
1
1
Order By: Relevance
“…Moreover, cationic nanoparticles first induce the release from the lysosome of smaller cleaved‐cathepsin D (~27 kDa), followed later by the larger cathepsin B (~37 kDa) . A recent study reported that the lysosomotropic compound l ‐leucyl‐ l ‐leucine O ‐methyl ester renders lysosomes permeable to protons prior to the release of preloaded dextrans, and that ESCRT machinery is initiated to repair the damaged membrane . These findings suggest that LMP is a progressive and dynamic process and they also point to the existence of a molecular “sieve” that dictates the specific translocation of the lysosomal contents.…”
Section: Lysosomal Dysfunction and Lmpmentioning
confidence: 95%
“…Moreover, cationic nanoparticles first induce the release from the lysosome of smaller cleaved‐cathepsin D (~27 kDa), followed later by the larger cathepsin B (~37 kDa) . A recent study reported that the lysosomotropic compound l ‐leucyl‐ l ‐leucine O ‐methyl ester renders lysosomes permeable to protons prior to the release of preloaded dextrans, and that ESCRT machinery is initiated to repair the damaged membrane . These findings suggest that LMP is a progressive and dynamic process and they also point to the existence of a molecular “sieve” that dictates the specific translocation of the lysosomal contents.…”
Section: Lysosomal Dysfunction and Lmpmentioning
confidence: 95%
“…The lysosomotropic compound LLOME (L-leucyl-L-leucine O -methyl ester) is commonly used to rupture endolysosomes (3, 23, 24). LLOME rapidly permeates cellular membranes and accumulates in the lumen of acidified organelles, where it is condensed into a membranolytic polymer by the lysosomal enzyme cathepsin C (9, 23). We confirmed LLOME-induced damage in HeLa cells by noting concentration of cytoplasmic GAL3 (a galectin frequently used to monitor damage (24)) on punctate structures (Fig.…”
Section: Escrts Respond To Endolysosomal Damagementioning
confidence: 99%
“…The effects of LLOME on ESCRTs were abolished by preincubating cells with the cathepsin inhibitor E64d (Fig. 1D), which prevents LLOME processing by cathepsin C and consequent membrane disruption (9). Accordingly, ESCRT-enriched structures induced by LLOME corresponded to late endosomes and lysosomes, coinciding well with LAMP1 but not with the early endosome protein EEA1 (Fig.…”
Section: Escrts Respond To Endolysosomal Damagementioning
confidence: 99%
See 2 more Smart Citations